Social cognition in cervical dystonia - Laura Mahady; Jessica White; Shameer Rafee; Siew-Mei Yap; Sean O'Riordan; Michael Hutchinson; Patricia Gough; Fiadhnait O'Keeffe (Clinical Parkinsonism & Related Disorders, 2023)
Background: Whilst traditionally considered a movement disorder, it is now generally accepted that cervical dystonia (CD) presents with additional non-motor symptoms which significantly impact quality of life. Our study primarily aimed to explore social cognition and levels of psychological distress in individuals with CD, in comparison to age- and sex-matched healthy controls. Methods: 20 participants with CD attending a specialist movement disorders clinic were recruited. 20 age and sex matched neurologically healthy controls were recruited in parallel. Participants completed the Hospital Anxiety and Depression Scale, and two novel social cognition tasks: The Cambridge Mindreading Face-Voice Battery (CAFMB) and the Edinburgh Social Cognition Test (ESCoT). Results: Participants with CD exhibited poorer complex emotion recognition abilities for visual and auditory stimuli, compared to controls on the CAFMB task. Participants with CD did not differ significantly from controls on performance on cognitive or affective Theory of Mind tasks, or interpersonal or intrapersonal understanding of social norms, as measured by the ESCoT. The proportion of depressive symptoms was significantly higher for participants with CD than controls. 40% of participants with CD reported clinically elevated depressive symptoms, and 60% reported clinically elevated anxiety. Poorer understanding of emotional facial expressions was associated with higher levels of depression in the CD group. Conclusions: Significant between-group differences between participants with CD and controls suggests socio-cognitive dysfunction is an important aspect of the non-motor syndrome of CD. Findings highlight the need for assessment of and intervention for both social cognitive difficulties and psychological distress in individuals with CD.